In-school asthma management and physical activity: children's perspectives. (14th May 2014) - Walker, Timothy J.; Reznik, Marina
Abstract: Objective : Regular physical activity (PA) is an important component of pediatric asthma management. No studies have examined how in-school asthma management influences PA from children's perspectives. The aim of this study was to explore children's perceptions of the impact of in-school asthma management on PA. Methods : Qualitative interviews with 23 inner-city minority children with asthma (aged 8–10 yrs; 12 girls, 11 boys) were conducted in 10 Bronx, New York elementary schools. Sampling continued until saturation was reached. Interviews were recorded, transcribed and independently coded for common themes. Results : Interviews produced five themes representing students' perceptions about (1) asthma symptoms during in-school PA; (2) methods to control asthma episodes during school PA; (3) methods to prevent asthma episodes during school; (4) limited accessibility of asthma medications; and (5) negative feelings about asthma and medication use. The majority of students experienced asthma symptoms while performing PA during school. Primary methods of managing asthma symptoms were sitting out during activity, drinking water, and visiting the nurse. Students lacked awareness or adherence to action plans to prevent or control asthma. Students reported limited access to medication during school and feelings of embarrassment and/or concerns of teasing when medicating in front of others. Conclusions : Our results indicate inappropriate in-school management of asthma symptoms, poor asthma control, lack of accessible medication, and stigma around publicly using asthma medication. Thus, students often missed or were withheld from PA. Interventions to improve in-school asthma care must consider ways to address these issues.